I wonder why flutes have holes : and other questions about music - Paker, Josephine (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Flutes Have Holes is jam-packed with fascinating facts about music, from 'Are rattles just for babies?' to 'Which composer was deaf?'
Includes index
Keywords: Music